2006
DOI: 10.1200/jco.2006.24.18_suppl.10574
|View full text |Cite
|
Sign up to set email alerts
|

Phase I pharmacokinetic (PK), and pharmacodynamic (PD) trial of the novel oral Notch inhibitor MK-0752 in patients (pts) with advanced breast cancer (BC) and other solid tumors

Abstract: 10574 Introduction: Activation of Notch signaling occurs in ∼40% of human BCs and high Notch expression is associated with poor outcome. Inhibition of Notch inhibits BC cell proliferation in vitro. Notch signaling requires gamma secretase (GS), which cleaves Notch, releasing the Notch intracellular domain (NICD) to activate transcription of target genes. MK-0752 is a potent GS inhibitor. Methods: In Part 1 of the study, pts with advanced solid tumors were enrolled using an accelerated dose escalation with 1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Based on our recent findings that ex vivo CLL cells have a functional ER stress-triggered caspase cascade initiated by caspase-4 and involving caspase-8 and -3, 24 we first investigated whether GSI I potentiates the activation of these caspases (patients [1][2][3][4][5][6][7][8][9][10][11][12]. Time-course analysis shows that the cleavage of caspase-4 into its active 20-kDa subunit was increased by GSI I, compared with controls, already after 1 hr and continued to be increased until 24 hr ( Fig.…”
Section: Gsi I Rapidly Increases Apoptotic Er Stress Signaling In Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our recent findings that ex vivo CLL cells have a functional ER stress-triggered caspase cascade initiated by caspase-4 and involving caspase-8 and -3, 24 we first investigated whether GSI I potentiates the activation of these caspases (patients [1][2][3][4][5][6][7][8][9][10][11][12]. Time-course analysis shows that the cleavage of caspase-4 into its active 20-kDa subunit was increased by GSI I, compared with controls, already after 1 hr and continued to be increased until 24 hr ( Fig.…”
Section: Gsi I Rapidly Increases Apoptotic Er Stress Signaling In Cllmentioning
confidence: 99%
“…6 A dysregulated Notch signaling has been associated with the pathogenesis of several malignancies, 7 and GSIs have been shown to inhibit the growth and/ or survival of several tumor cells, 8 including CLL cells. 9 Some GSIs have also been tested in phase I trials for patients with breast cancer 10 and T-cell acute leukemias. 11 However, in these malignancies, minimal clinical responses have been observed, and other studies have also suggested that Notch inhibition is therapeutically effective only when combined with inhibition of other relevant pathogenic pathways.…”
mentioning
confidence: 99%
“…Although numerous drugs are in development, significant challenges still exist before a Notch-targeted therapeutic strategy can be clinically applied. For example, patients with BC receiving continuous doses of MK-0752 at 450 mg/daily present with symptoms of toxicity and fatigue (160). Furthermore, gastrointestinal toxicity is also a major side effect in patients treated with GSIs (161).…”
Section: Application Of Notch Signaling In the Clinical Treatment Of mentioning
confidence: 99%
“…Though many drugs are in development, enormous challenges remain before a Notchtargeted therapeutic strategy can be clinically applied. BC patients receiving continuous doses of MK-0752 at 450 mg daily present significant symptoms of toxicity and fatigue [95]. Further, gastrointestinal toxicity is also a major side effect in patients being treated with GSIs [96].…”
Section: Conclusion and Clinical Developmentmentioning
confidence: 99%